Theater im "Dritten Reich" : Theaterpolitik, Spielplanstruktur, NS-Dramatik - Eicher, Thomas 1963- VerfasserIn; Panse, Barbara 1949- VerfasserIn; Rischbieter, Henning 1927-2013 VerfasserIn HerausgeberIn (Kallmeyer, 2000)
Literaturverzeichnis: Seite 723-743